THE EFFECT OF GADGET BAN POLICY ON STUDENTS' LEARNING MOTIVATION AND SOCIAL BEHAVIOR AT SMPN 1 LEMBANG, WEST BANDUNG REGENCY - Dinna Daniati; Lili Halimah; Khaerul Syobar (SOSIOEDUKASI, 2026)
This study investigates the effect of a school-level gadget ban policy on the learning motivation and social behavior of students at SMPN 1 Lembang, West Bandung Regency. In the digital era, uncontrolled smartphone usage has led to cognitive distraction, reduced attention spans, and an increase in negative social interactions such as cyberbullying among adolescents. Utilizing an explanatory quantitative approach with a cross-sectional design, data were collected from 302 students selected through proportionate stratified random sampling. The primary instrument was a valid and reliable Likert-scale questionnaire, supported by structured observation and documentation. Data were analyzed using simple linear regression. The results indicate that the gadget ban policy, implemented through a strict "bell-to-bell" mechanism, has a positive and significant effect on student learning motivation, contributing 32% to the variance. By removing the instant dopamine distractions of digital devices, students demonstrated improved intrinsic and extrinsic motivation, perseverance, and deep focus (flow) during lessons. Furthermore, the policy exerts a more substantial positive and significant effect on students' social behavior, accounting for 43% of the variance. The absence of gadgets effectively mitigates the phubbing phenomenon, forcing a restoration of face-to-face communication, enhancing empathy, fostering pro-social cooperation, and significantly reducing incidences of cyberbullying. In conclusion, the institutional regulation of digital devices serves not only as a disciplinary measure but also as a crucial pedagogical strategy that simultaneously optimizes academic drive and cultivates a harmonious, resilient social character within the educational ecosystem.